Improvements on effective permittivity measurements of powdered alumina: Implications for bulk permittivity properties of asteroid regoliths. Issue 1 (1st January 2017) - Hickson, Dylan; Sotodeh, Shahroukh; Daly, Michael G.; Ghent, Rebecca; Nolan, Michael C.
Abstract: Accurate measurements of the dielectric properties of materials are essential in constraining interpretations of radar observations of planetary bodies. For bodies whose surfaces are comprised of regolith this requires an understanding of the behaviour of the bulk permittivity of powders. In this research we measure the effective permittivity of powdered aluminium oxide (or alumina, Al 2 O 3 ) in a 7 mm and 14 mm (diameter) coaxial airline at 7.5 GHz for multiple samples with varying grain size. The dielectric constant of alumina is extracted from these measurements using the Bruggeman (Effective Medium Approximation) mixing equation. We develop a model to account for heterogeneity within the airline, specifically in regards to local variation in porosity. The results of the model show good correlation to experimental data and effectively correct for grain size effects on the measured bulk permittivity. We show that particle shape can have a significant impact on the output of the model and can be accounted for by modelling particles as ellipsoids rather than perfect spheres, where the depolarization factor must be measured and averaged for a specific sample batch.